Velocity, aerobic power and metabolic cost of whole body and arms only front crawl swimming at various stroke rates - Morris, K. S.; Osborne, M. A.; Shephard, M. E.; Skinner, T. L.; Jenkins, D. G. (European Journal of Applied Physiology, 2016)
Purpose: Stroke rate (SR) has not been considered in previous research examining the relative roles of the limbs in front-crawl performance. This study compared velocity, aerobic power (VO2) and metabolic cost (C) between whole body (WB) and arms only (AO) front-crawl swimming across various intensities while controlling SR. Methods: Twenty Australian national swimmers performed six 200 m front-crawl efforts under two conditions: (1) WB swimming and, (2) AO swimming. Participants completed the 200 m trials under three SR conditions: "low" (22-26 stroke-cycles min-1), "moderate" (30-34 stroke-cycles/min and "high" (38-42 stroke-cycles min-1). VO2 was continuously measured, with C, velocity, SR, and kick rate calculated for each effort. Results: Regardless of the SR condition and sex, AO velocity was consistently lower than WB velocity by ~11.0 % (p < 0.01). AO VO2 was lower than WB VO2 at all SR conditions for females (p < 0.01) and at the "high" SR for males (p < 0.01). C did not differ between WB and AO at any SR for both sexes (p > 0.01). When C was expressed as a function of velocity, WB and AO regression equations differed for males (p = 0.01) but not for females (p = 0.087). Kick rate increased as SR increased (p < 0.01), though the kick-to-stroke rate ratio remained constant. Conclusion: Elite swimmers gain ~11 % in velocity from their kick and, when used in conjunction with the arm stroke at the swimmers` preferred frequency, the metabolic cost of WB and AO swimming is the same. Coaches should consider these results when prescribing AO sets if their intention is to reduce the metabolic load.